1986
DOI: 10.1128/mcb.6.1.105
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of transcriptional activity and stable complex formation by 5'-flanking regions of mouse tRNAHis genes.

Abstract: We determined the nucleotide sequences of three mouse tRNA His genes and a tRNAGIl gene present in two different A clones. One A clone contained two tRNA His genes 600 base pairs (bp) apart in opposite orientations. The other clone contained a tRNAHIs and a tRNAGIy gene 569 bp apart in the same orientation. The coding regions of the three tRNAHis genes were identical to sequenced mammalian tRNAHiS if posttranscriptional modifications are not considered. Notably, the three tRNAHiS genes and a fourth gene previo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

1987
1987
1998
1998

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 50 publications
0
16
0
Order By: Relevance
“…The level of this transcription is approximately the same as that of the consensus U6 clone that possesses all known 5' promoter elements (pGEM/U6). However, many studies have shown an effect of flanking sequences on the transcription of genes with internal promoters (1,12,26,31 [for review, see reference 13]), and we decided to systematically investigate whether or not this is the case with 87U6. Figure 1 provides a summary of these results.…”
Section: Resultsmentioning
confidence: 99%
“…The level of this transcription is approximately the same as that of the consensus U6 clone that possesses all known 5' promoter elements (pGEM/U6). However, many studies have shown an effect of flanking sequences on the transcription of genes with internal promoters (1,12,26,31 [for review, see reference 13]), and we decided to systematically investigate whether or not this is the case with 87U6. Figure 1 provides a summary of these results.…”
Section: Resultsmentioning
confidence: 99%
“…There is increasing evidence, however, that 5' and 3' flanking sequences also contribute to tRNA promoter function. Alteration of normal 5' flanking sequences diminishes or abolishes transcription of Drosophila, yeast, mouse, human and silkworm tRNA genes, showing that elements in this region provide positive transcription signals (1,2,3,4,5,6,7,8,9,10). Moreover, flanking sequences must be responsible for the fact that members of tRNA gene families that contain identical coding sequences frequently exhibit different transcription efficiencies.…”
Section: Introductionmentioning
confidence: 99%
“…Such members have identical, or nearly identical, mature tRNAcoding regions and, accordingly, identical A-and B-box ICRs. The majority of sequence differences in these gene families occur within the DNA flanking the gene; indeed, the differential in vitro expression of Drosophila tRNALYS, tRNAArg, and tRNAASn, Bombyx tRNAAIa, Xenopus tRNATYr, and mouse tRNAH1S genes has been attributed specifically to 5'-flanking sequence differences (12,13,20,25,27,51).…”
Section: Discussionmentioning
confidence: 99%
“…These results suggested that all the sequences necessary for tRNA gene transcription were contained within the sequence encoding the RNA. Although the ICR A-and B-box sequences are essential for tRNA gene transcription, in vitro studies with Drosophila, Bombyx, Saccharomyces, Xenopus, and mouse tRNA genes provide evidence that tRNA gene transcription is also dependent upon sequences that extend beyond the A-and B-box ICRs (11,20,27,41,49). In particular, 5'-flanking sequences can modulate the transcriptional activity of tRNA genes dramatically (13, 51).…”
mentioning
confidence: 99%